Construção de uma unidade de ensino potencialmente significativa para o experimento de Hertz - Toledo, Sérgio Soares de (2018)
Teaching exists when meaningful learning occurs. Based on this idea, we propose the construction and application of a UEPS (teaching potentially significant unit) for teaching physics in the content of electromagnetic waves. A UEPS is a kind of approach that makes connections between students' prior knowledge and new scientific information, with the student as the main focus, with the intention of contributing significantly to the construction of knowledge. Within this context we include the practice of the hertz experiment with adaptations in order to further enrich the teaching unit in order to obtain good results in students'. We report the experience lived in the classroom during the application of the UEPS through written questions, comments, testimonials of the students, records of class moments through photos and notes, written evaluation and experimental presentation.